1983
DOI: 10.1524/ract.1983.32.13.25
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Superheavy Elements

Abstract: Superheavy elements /Predicted properties /Search for superheavy elements in nature ¡Attempted syntheses by heavy-ion reactions SummaryExtensive experimental efforts have been made during the past 12 years to detect superheavy elements in nature and to produce them in heavy-ion collisions. The search in nature remained inconclusive. Attempts to synthesize superheavy elements in the laboratory produced negative results. The concurrent study of heavy-ion reaction mechanisms has suggest new synthetic routes and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…7a and 7d and discuss the consequences of both these assumptions concerning the chances to produce surviving superheavy nuclei by fusion reactions between 48Ca projectiles and heavy actinide targets. One of the presently most extensively investigated combination [56] is 48Ca +24SCm leading to element 116 with the neutron (23) and (24) of 0.2 MeV and 13 MeV, respectively. In the latter case, the 13 MeV additional energy needed to fuse drastically reduces the chances to produce surviving superheavy evaporation residues because the excitation energy at the fusion barrier would increase to 39 MeV.…”
Section: Consequences For the Production Of Superheavymentioning
confidence: 99%
“…7a and 7d and discuss the consequences of both these assumptions concerning the chances to produce surviving superheavy nuclei by fusion reactions between 48Ca projectiles and heavy actinide targets. One of the presently most extensively investigated combination [56] is 48Ca +24SCm leading to element 116 with the neutron (23) and (24) of 0.2 MeV and 13 MeV, respectively. In the latter case, the 13 MeV additional energy needed to fuse drastically reduces the chances to produce surviving superheavy evaporation residues because the excitation energy at the fusion barrier would increase to 39 MeV.…”
Section: Consequences For the Production Of Superheavymentioning
confidence: 99%
“…With current sensitive methods nuclides like "'Pu can be detected at a level of 10' atoms [4] after chemical Separation from environmental samples. In extreme cases chemical methods have to be applied at a level of a few atoms at a time, e. g., in recent attempts to produce superheavy elements in the laboratory [5], In this context the question arises: Do such extremely small amounts of an element follow its chemical behaviour in macroscopic concentrations, and are Separation procedures worked out at ordinary concentrations applicable at much lower levels? An argument for differences in the behaviour may be the following [6]: Although the behaviour of each individual atom in a Separation step is governed by Statistical rules, the chemistry at macroscopic levels, about 10" atoms and beyond, is very reproducible due to the large number of atoms that undergo the Statistical distribution process involved.…”
Section: Introductionmentioning
confidence: 99%
“…More recent reviews can be found in Refs. [26,271 and reviews of the heaviest elements recently synthesized in Refs. 128-311.…”
Section: I419mentioning
confidence: 99%